2009
DOI: 10.1590/s0034-72802009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Facectomia na infância: quem são nossos pacientes?

Abstract: RESUMOObjetivo: Analisar o perfil dos pacientes até 10 anos de idade, submetidos à facectomia no setor de catarata do Hospital da Piedade, determinando as principais indicações, perfil sócioeconômico e características pré-natais nos casos relevantes. Métodos: Foram analisados retrospectivamente, os dados de 60 pacientes com até 10 anos de idade, submetidos à lensectomia, dentro do período de janeiro de 2006 a dezembro de 2007. Todas as cirurgias foram realizadas no setor de catarata do Hospital da Piedade, pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
2
0
3
Order By: Relevance
“…Ocular injury is the leading cause of unilateral blindness in children (Jandeck et al, 2000). It is estimated that ocular injuries are avoidable in up to 90% of cases avoiding the mechanisms of damage to the ocular structures (Saxena et al, 2002;Santhiago et al, 2009;Abbott et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ocular injury is the leading cause of unilateral blindness in children (Jandeck et al, 2000). It is estimated that ocular injuries are avoidable in up to 90% of cases avoiding the mechanisms of damage to the ocular structures (Saxena et al, 2002;Santhiago et al, 2009;Abbott et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This issue was addressed in a retrospective study conducted at Piedade Hospital between 2006 and 2007, which found that the average time between the suspicion of congenital cataract by a paediatrician or layman and ophthalmic examination was 3 months. Therefore, screening protocols are critical to avoid this long waiting period and to promote the child's well-being (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Assim, com relação aos pacientes, faz-se necessário: -conscientizar a população sobre a doença e a possibilidade de cura, estimulando a procura pelo tratamento (3)(4)(5)(6)(7)(8) ;…”
Section: Importância Do Centro Cirúrgico Ambulatorial Para a Realizaçunclassified
“…-promoção de cirurgia economicamente acessível (2)(3)(4)(5)(6)(7)(8)(9) ; -oferta de cirurgia de boa qualidade, que proporcione resultados satisfatórios, utilizando novas tecnologias, e estimule a procura pelo tratamento (2,(10)(11)(12)(13)(14)(15)(16)(17)(18) .…”
Section: Importância Do Centro Cirúrgico Ambulatorial Para a Realizaçunclassified